2015
DOI: 10.1101/gad.264929.115
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for Mob1-dependent activation of the core Mst–Lats kinase cascade in Hippo signaling

Abstract: The Mst-Lats kinase cascade is central to the Hippo tumor-suppressive pathway that controls organ size and tissue homeostasis. The adaptor protein Mob1 promotes Lats activation by Mst, but the mechanism remains unknown. Here, we show that human Mob1 binds to autophosphorylated docking motifs in active Mst2. This binding enables Mob1 phosphorylation by Mst2. Phosphorylated Mob1 undergoes conformational activation and binds to Lats1. We determine the crystal structures of phospho-Mst2-Mob1 and phospho-Mob1-Lats1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
251
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(276 citation statements)
references
References 55 publications
18
251
1
6
Order By: Relevance
“…We have previously shown that upon phosphorylation at its activation loop in the kinase domain, Hpo/MST undergoes multisite autophosphorylation in an unstructured linker region between the kinase domain and the SARAH domain (Ni et al, 2015). Some of these sites serve as phospho-dependent docking sites that function together with a hydrophobic motif (HFM) (Figure 1A) to recruit Mats/MOB1 thus promoting Wts/LATS phosphorylation (Ni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that upon phosphorylation at its activation loop in the kinase domain, Hpo/MST undergoes multisite autophosphorylation in an unstructured linker region between the kinase domain and the SARAH domain (Ni et al, 2015). Some of these sites serve as phospho-dependent docking sites that function together with a hydrophobic motif (HFM) (Figure 1A) to recruit Mats/MOB1 thus promoting Wts/LATS phosphorylation (Ni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these sites serve as phospho-dependent docking sites that function together with a hydrophobic motif (HFM) (Figure 1A) to recruit Mats/MOB1 thus promoting Wts/LATS phosphorylation (Ni et al, 2015). While investigating the functional contribution of the remaining phosphorylation sites in the linker region, we found that, contrary to the Mats/MOB1 docking sites, these autophosphorylation sites play an opposite role in Hippo signaling.…”
Section: Introductionmentioning
confidence: 99%
“…3; Ni et al 2015). MST2 autophosphorylates its long linker between the kinase domain and the SARA domain to generate a phosphor-docking motif, which can recruit MOB1.…”
Section: Mechanisms Of Hippo Kinase Cascade Activationmentioning
confidence: 99%
“…MST1/2 or MAP4Ks activate LATS1/2 by phosphorylating the hydrophobic motif residues in LATS1/2 [8][9][10][11][12][13][14]. Activated LATS1/2 then phosphorylate YAP and TAZ, leading to 14-3-3 binding and cytoplasmic retention [15].…”
Section: Introductionmentioning
confidence: 99%